Identification of Waste Supply Chain Flow to Improve Performance - Ratih Setyaningrum; Recky Gumantara; Dwi Nurul Izzhati; Dian Retno Sawitri (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2022)
Semarang city has the amount of waste that piled up in the Landfill as much as 850 tons/day with the amount of unmanaged waste as is 100 tons/day. This phenomenon needs to be identified and evaluated for the flow of waste disposal from upstream to downstream. Therefore, the purpose of this study is to identify the flow of the waste supply chain and simulate it to determine the performance of waste handling in an area. The research method begins with a supply chain questionnaire which will then be statistically tested to be used as input for supply chain flow generation and simulation using Arena software. Based on the identification of the supply chain, the flow of the waste supply chain in the Wonosari area of Semarang is from households to the garbage dump to be taken to the landfill as far as 10 km. From the landfill, it is further processed into a selling value product. In this study, waste from the landfill is also the input material for the paving block production workshop (WPBP FT) at the Faculty of Engineering, Dian Nuswantoro University. Plastic waste will be used as a mixed material for making paving blocks. The supply chain simulation results using Arena show that the performance is good.